The Chaplain Family Project: Development, Feasibility, and Acceptability of an Intervention to Improve Spiritual Care of Family Surrogates. Issue 4 (2nd October 2019) - Torke, Alexia M.; Maiko, Saneta; Watson, Beth N.; Ivy, Steven S.; Burke, Emily S.; Montz, Kianna; Rush, Sarah A.; Slaven, James E.; Kozinski, Kathryn; Axel-Adams, Robyn; Cottingham, Ann
Abstract : In the Intensive Care Unit (ICU), family members experience psychological and spiritual distress as they cope with fear, grief, and medical decisions for patients. The study team developed and pilot tested a semistructured chaplain intervention that included proactive contact and spiritual assessment, interventions, and documentation. An interdisciplinary team developed the intervention, the Spiritual Care Assessment and Intervention (SCAI) Framework. Three chaplains delivered the intervention to surrogates in two ICUs. There were 25 of 73 eligible patient/surrogate dyads enrolled. Surrogates had a mean age of 57.6, were 84% female and 32% African American. The majority (84%) were Protestant. All received at least one chaplain visit and 19 received three visits. All agreed they felt supported by the chaplains, and qualitative comments showed spiritual and emotional support were valued. A semistructured spiritual care intervention for ICU surrogates is feasible and acceptable. Future work is needed to demonstrate the intervention improves outcomes for surrogates and patients.